Efficacy of graphene oxide as an antiviral alternative against equine herpesvirus-1 (ehv-1) - Muhammad Shahin Kamarul-Anuar (2023)
An abstract of the research paper presented to the Faculty of Veterinary Medicine, Universiti Malaysia Kelantan, in partial requirement on the course DVT 55204 - Research Project. Equine herpesvirus-1 (EHV-1) is one of the most important and prevalent viral pathogens of horses and a major threat to the equine industry throughout most of the world. This infectious virus, especially strains of EHV-1 and 4 pose the most serious health risk for domestic horses. EHV-1 primarily causes respiratory disease but viral spread to distant organs enables the development of more severe sequelae; abortion and neurologic disease. The treatment has been partially successful due to the nature of virus that replicates within the host cells, restricting drug permeation. Therefore, it is important to find alternatives to the existing treatment. Graphene oxide (GO) is a carbon based nanoparticle that has been investigated for application in biomedical application. For this research, we aimed to demonstrate the virucidal and prophylactic activity of GO and toxicity impact of the compound towards mammalian cell growth. Procedures performed include Resazurin assay for cytotoxic assay, GO treatment and polymerase chain reaction (PCR). Based on the results, GO demonstrated virucidal activity at 400 ug/mL but not prophylactic capability. Also, at 400 ug/mL GO also demonstrated less toxicity effect towards the mammalian cells, evidenced by cell growth at the concentration tested. Due to the high concentration required for virucidal activity, ultimately it is not effective to be used as a treatment against EHV-1. Therefore, GO is not recommended to be used against EHV-1 infections. Keywords: Graphene Oxide, Vero cells, virucidal activity, antiviral, Equine herpesvirus-1, toxicity cell growth